Music listening as self-enhancement: Effects of empowering music on momentary explicit and implicit self-esteem. (May 2018) - Elvers, Paul; Fischinger, Timo; Steffens, Jochen
In everyday life people use music to adjust their levels of arousal, to regulate their mood and emotions, and to cope with previous experiences, indicating that music plays an important role for everyday wellbeing. While the relationship between music and emotions has received considerable interest in past decades, little is known about the self-esteem boosting function of empowering music. In the present study, we investigated the relationship of music listening and self-esteem, by examining how momentary explicit and implicit self-esteem are (a) influenced by the expressive properties of music and (b) predicted by individual differences in responses to music. Results indicate that both explicit and implicit self-esteem are affected by music listening but in different ways. While momentary explicit self-esteem changed as a function of the expressive properties of the music and was positively predicted by liking, implicit self-esteem was positively predicted by empathy and negatively predicted by nostalgia. In contrast to changes in self-esteem, no changes in mood were observed. We anticipate our findings to be a starting point for further investigations of the cognitive and affective processes involved when listening to empowering music.